(untitled) (Scientia Agropecuaria, 2025)
The formation of toxic compounds such as acrylamide (AA) and hydroxymethylfurfural (HMF) during thermal food processing (>120 °C) represents a significant risk to human health, as they have been associated with neurotoxic, genotoxic, and carcinogenic effects. However, several studies have shown that polyphenols can reduce the levels of these toxic compounds. In this context, this review examines the potential of polyphenols to mitigate the formation of AA and HMF via distinct mechanisms during the Maillard reaction (MR). In general, these compounds interact with precursors and intermediates of the MR. Thus, polyphenols represent a natural and effective strategy for improving food safety, thereby promoting the development of healthier products. However, Future challenges remain, including the elucidation of the chemical mechanisms involved in the action of polyphenols, an in-depth study of factors such as pH, temperature, and food matrix, toxicological and metabolic evaluations, regulatory aspects, the use of clean and sustainable technologies for obtaining polyphenols, optimization of extraction methods, and application in food matrices while considering sensory effects. A multidisciplinary approach will be vital to achieving the effective and safe application of polyphenols in the food industry.